Advancing gender equity in sport: a scoping review of international sport federation policies for pregnant, postpartum and parenting elite athletes - Davenport, M. H.; Bains, G.; Hayman, M.; Cai, C.; Mkumbuzi, N. S.; McHugh, T.-L. (British Journal of Sports Medicine, 2025)
Objective The aim was to synthesise international-level sport policies for pregnant, postpartum or parenting high-performance athletes in order to understand what policies currently exist and to identify policy gaps to be addressed.